Cartographic mismatches and language policy: the case of Hindi in Singapore - Jain, Ritu (2017)
In this paper, we present Singapore’s language policy as a case of flexible responsiveness to demographic and societal shifts as a result of high migration. The particular need to accommodate the enhanced linguistic diversity among the linguistically heterogeneous Indians, previously served by Tamil, has led to the ‘semiofficial’ representation of Hindi, Punjabi, Bengali, Gujarati, and Urdu in the language policy in recent years. Notwithstanding the choices, a majority of the target Indians prefer Hindi over the familial languages as the national status of Hindi in India better meets the multilingual aspirations of transmigrants with uncertain itineraries. The language choices of Indian parents indicate that language values derive from the range of mobility (e.g., translocal or transnational) that languages have promoted or are perceived to help chart in the future. Adopting the metaphor of cartographies of language used by Park (2014), we suggest that these cartographic perceptions pose a challenge to language policies. We attribute the cartographic mismatches between policy and individual goals to distinctions between language valuations. Through an analysis of school enrolment data and ethnographic interviews, we suggest that language in education decisions of transmigrant populations are mediated through valuations of languages that allow the widest radius of mobility across multiple sites rather than attachments to linguistic, ethnic, or national communities.